1996
DOI: 10.1159/000177139
|View full text |Cite
|
Sign up to set email alerts
|

Non-Lipid-Related Effects of 3-Hydroxy-3-Methylglutaryl Coenzyme A Reductase Inhibitors

Abstract: With the increasing knowledge of the pathogenesis of atherosclerosis, it appears that in the future the prevention of cardiovascular disease will involve not only risk factor correction, but also direct pharmacological control of processes occurring in the arterial wall. Among these, a pivotal role is played by smooth muscle cell (SMC) migration and proliferation, which, together with lipid deposition, are prominent features of atherogenesis and restenosis after angioplasty. Mevalonate and other intermediates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 47 publications
(78 reference statements)
2
42
0
2
Order By: Relevance
“…These drugs arc used for the treatment of hypercholesterolemia (21,33), and clinical trials have demonstrated that they can induce regression of vascular atherosclerosis as well as reduce cardiovascular morbidity and mortality in patients with CAD and other cardiovascular diseases (21,32,34,35). Slight and/or statistically significant decrease of cholesterol, HDL and LDL as well as CHOL/PL observed 6 months after the treatment partly agrees with data in literature.…”
Section: Resultssupporting
confidence: 83%
“…These drugs arc used for the treatment of hypercholesterolemia (21,33), and clinical trials have demonstrated that they can induce regression of vascular atherosclerosis as well as reduce cardiovascular morbidity and mortality in patients with CAD and other cardiovascular diseases (21,32,34,35). Slight and/or statistically significant decrease of cholesterol, HDL and LDL as well as CHOL/PL observed 6 months after the treatment partly agrees with data in literature.…”
Section: Resultssupporting
confidence: 83%
“…In some bench studies, statins have been shown to possess immune modifying 17,18 and antiinflammatory effects. 17,19,20 Recent clinical studies show a differential effect of statins on CRP-associated risk, supporting this antiinflammatory hypothesis. 6,21 Although statin therapy appears to reduce CRP-related events, no study has evaluated the effect of statins on infection-related events.…”
mentioning
confidence: 85%
“…6,15,16,21 In addition to lowering cholesterol, statins have been postulated to have a variety of other beneficial effects, including antiinflammatory effects. 17,19,20 Several studies suggest that statins reduce events associated with elevated CRP 6,21 and that they reduce plasma concentrations of CRP. 22 These findings reveal a strong potential for the use of statins in the treatment of CRP-related risk.…”
Section: Statins and Cadmentioning
confidence: 99%
“…Only the presence of geranylgeraniol or farnesol in the medium containing statins leads to an almost-complete restoration of the mitogenic response. 25 Farnesol and geranylgeraniol interact with the hydrophilic Ras protein family and become covalently linked. The acquisition of lipophilicity by the complex allows the interaction of Ras proteins with cellular membranes.…”
Section: Pleiotropic Effects Of Statinsmentioning
confidence: 99%